EFEKTIVITAS PEMBELAJARAN PAI MELALUI MEDIA POWERPOINT PADA PESERTA DIDIK KELAS VI UPTD SD NEGERI 3 MAKMUR - Suraya, Naili; Lestari, Maya; Mandarwati (Journal of Contemporary Indonesian Islam, 2023)
The integration of PowerPoint as an innovative tool has significantly transformed Islamic Religious Education (IRE) learning. Teachers can capture students’ attention by presenting content in a more visual and interactive manner, incorporating text, images, animations, and live quizzes. This makes IRE material more engaging, efficient, and time-saving. The purpose of this study is to explore and analyze the benefits of utilizing innovative media in teaching IRE, with a particular focus on PowerPoint as the primary medium. Conducted through a qualitative field study at UPTD SD Negeri 3 Makmur, Bireuen, the research investigates how PowerPoint enhances the teaching and learning process, from fostering student motivation to improving comprehension. Findings reveal that PowerPoint-based innovation produced positive and responsive outcomes among sixth-grade students. While previous lessons often felt abstract due to lengthy verbal explanations, the integration of videos and visuals made concepts more concrete, accessible, and effective for learners.